Caspofungin induces the release of Ca2+ ions from internal stores by activating ryanodine receptor-dependent pathways in human tracheal epithelial cells - Peters, Sabrina; Koch, Christian; Weiterer, Sebastian; Weigand, Markus A.; Sander, Michael; Henrich, Michael (Scientific reports, 2020)
The antimycotic drug caspofungin is known to alter the cell function of cardiomyocytes and the cilia-bearing cells of the tracheal epithelium. The objective of this study was to investigate the homeostasis of intracellular Ca2+ concentration ([Ca2+]i) after exposure to caspofungin in isolated human tracheal epithelial cells. The [Ca2+]i was measured using the ratiometric fluoroprobe FURA-2 AM. We recorded two groups of epithelial cells with distinct responses to caspofungin exposure, which demonstrated either a rapid transient rise in [Ca2+]i or a sustained elevation of [Ca2+]i. Both patterns of Ca2+ kinetics were still observed when an influx of transmembraneous Ca2+ ions was pharmacologically inhibited. Furthermore, in extracellular buffer solutions without Ca2+ ions, caspofungin exposure still evoked this characteristic rise in [Ca2+]i. To shed light on the origin of the Ca2+ ions responsible for the elevation in [Ca2+]i we investigated the possible intracellular storage of Ca2+ ions. The depletion of mitochondrial Ca2+ stores using 25 µM 2,4-dinitrophenol (DNP) did not prevent the caspofungin-induced rise in [Ca2+]i, which was rapid and transient. However, the application of caffeine (30 mM) to discharge Ca2+ ions that were presumably stored in the endoplasmic reticulum (ER) prior to caspofungin exposure completely inhibited the caspofungin-induced changes in [Ca2+]i levels. When the ER-bound IP3 receptors were blocked by 2-APB (40 µM), we observed a delayed transient rise in [Ca2+]i as a response to the caspofungin. Inhibition of the ryanodine receptors (RyR) using 40 µM ryanodine completely prevented the caspofungin-induced elevation of [Ca2+]i. In summary, caspofungin has been shown to trigger an increase in [Ca2+]i independent from extracellular Ca2+ ions by liberating the Ca2+ ions stored in the ER, mainly via a RyR pathway.